Pengaruh teknologi gamifikasi dalam meningkatkan motivasi dan hasil belajar numerasi siswa di sekolah dasar - Iswan S. Keku; Abdul Mansyur Panu; Rahmawati Harun; Dian Novian; Aziz Bouty (Trihayu: Jurnal Pendidikan Ke-SD-an, 2026)
This study examines the impact of technology intervention on elementary school students' learning motivation and numeracy skills using a quantitative quasi-experimental design. Fifty students were randomly assigned to an experimental group (technology-based learning) and a control group (conventional instruction). Statistical analysis revealed significant improvements in the experimental group: mean numeracy scores of 84.12 84.12 (vs. 75.48 75.48 in control, p < 0.05) and mean motivation scores of 88.56 88.56—more than double that of the control group. The key novelty of this research is the first empirical evidence confirming a strong causal link between technology intervention and simultaneous enhancements in motivation and numeracy among Indonesian elementary students, offering an innovative model for technology-integrated teaching in primary education contexts